Fitoquímica do caule de Citrus limonia enxertado com C. sinensis e da espécie de Nycticalanthus speciosus (RUTACEAE) e biossíntese de cumarinas preniladas - Ribeiro, Alan Bezerra (2006)
The Cravo lime species (C. limonia) acts as the grafting host, mostly used in the Brazilian citriculture and because of its precocious productivity, besides its good adaptation to most common soils, permitting for an optimum harvest. With the aim to contribute to the chemical knowledge of these graftings and to better understand its mechanisms, a phytochemical study of the rootstock from C. sinensis onto C. limonia were carried out. Earlier studies indicated the presence of a remarkable amount of prenylated compounds in the lower part of the C. sinensis graft, onto the C. limonia, while at the same time in the upper part these compounds was found in a very small amounts, rising to the assumption that these compounds could have been translocated from the host to the introduced graft species. In this way, biosynthetical studies of prenylated coumarines were also carried out aiming to evaluate the activity of the prenyltransferase enzyme, responsible by the incorporation of the isoprene units in these compounds. With the objective to advance our knowledge and chemical profile of the Rutaceae family, in which the Citrus genus is inserted. This study also describes the phytochemical and phytosystematics of the Nycticalanthus specious species pertaining to the same family. In the study of the rootstock, several different chromatographic methods were applied permitting to identify nine substances one of them being an unpublished flavanone. From the Nycticalanthus speciuous, eleven compounds were isolated as well as an indolopiridoquinazolic alkaloid and also three limonoids previously unheard of. The isolated compounds from the rootstock were assayed against the fungus Guignardia citricarpa, responsible for the black stains in Citrus species , with the objective to find a possible antifungus for this disease. Two coumarines showed premissory inhibitory activities. The biosynthetical study carried out with the prenyltransferase enzyme DMAPP, Umbelliferone and Herniarin showed that the translocation of the pyranocoumarine Xanthylentin should have happened. Seen in the different parts of the grafting of C. sinensis onto the C. limonia the enzyme were active only in the roots and with this observation, it appears that the coumarine is being metabolized in the lower part and translocated to the upper parts of the graft.